Pro-lactation cesarean section: Immediate skin-to-skin contact and its influence on prolonged breastfeeding - Zavala-Soto, José Octavio; Hernandez-Rivero, Laritza; Tapia-Fonllem, César (Frontiers in Sociology, 2022)
Mexico has a high rate of cesarean sections and one of the lowest prevalences of exclusive breastfeeding in all of Latin America. There are known factors that can compensate for the disadvantages and drawbacks of cesarean delivery over breastfeeding. In terms of studying the variations of breastfeeding experiences, this work specifically concentrates on exploring different changes in the technique of caesarean section, related to immediate Skin-to-Skin Contact for women with high and low risk pregnancies, which may in turn influence Maternal Satisfaction and the choice of Prolonged Breastfeeding. A convenience sample of (n = 150) women who underwent cesarean section in a private hospital in Mexico between the years 2015-2020 participated in this study, the participants answered a structured interview protocol designed for the specific purposes of this study. The analysis was guided grounded theory. The most common indications for cesarean section were those of active-phase arrest and regarding maternal complications, previous cesarean sections (n = 59) and hypertensive complications (n = 15) were the most frequent. For fetal complications, non-cephalic fetal positions (n = 12) were reported as the most common. Despite the different conditions of their caesarean sections, almost all the women experienced Skin-to-Skin Contact during the caesarean section. Almost all of them managed to breastfeed for more than six months. The main factors associated to prolonged breastfeeding and satisfaction were higher education degrees, immediate skin-to-skin contact during surgery and counseling on breastfeeding after the baby was born.